Probabilistic basis development of standardization of snow loads on building structures - Pichugin, Sergii (Academic journal Industrial Machine Building Civil Engineering, 2020)
Ensuring the reliability and safety of buildings and structures largely depends on a proper understanding of nature and quantitative description and rationing of loads on building structures, including snow loads. Analysis of the evolution of domestic snow load codes together with their statistical substantiation is an urgent task. The article contains a systematic review of codes and publications on the problem of snow load over the 80-year period from the 40s of the twentieth century to the present. The main attention is paid to the tendencies analysis of designing codes development concerning changes of territorial zoning and design coefficients, the appointment of normative and design values of snow load, and involvement in it of experimental statistical data. There is a high scientific level of domestic code DBN B.1.2-2006 "Loads and effects", which have a modern probabilistic basis and are associated with the codes of Eurocode. Scientific results that can be included in subsequent editions of snow load standards are highlighted.
Keywords: snow observations; snow load; territorial zoning; normative load; design load